2015
DOI: 10.1111/nmo.12555
|View full text |Cite
|
Sign up to set email alerts
|

Acute sacral nerve stimulation reduces visceral mechanosensitivity in Rat through spinal opioid pathway

Abstract: SNS impacts on visceral mechanosensitivity by decreasing the spino-bulbar reflex in response to CRD. Spinal opioid receptors are likely involved in this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Incontinence is often associated with hypersensitivity and SNS has been shown to reduce C‐fibers marker substance p levels in patients’ rectal mucosa . In addition, acute SNS is able to reduce visceral sensitivity in rats . Studying the effects of SNS in models of fecal incontinence would be of great interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incontinence is often associated with hypersensitivity and SNS has been shown to reduce C‐fibers marker substance p levels in patients’ rectal mucosa . In addition, acute SNS is able to reduce visceral sensitivity in rats . Studying the effects of SNS in models of fecal incontinence would be of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, no reliable predictive factor beyond the trial response has yet been identified for successful SNS . While several studies have identified key biological targets of SNS such as the endogenous opioid system , further delineation of the mechanisms of action of SNS is still needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fassov J performed SNS on 21 DIARRHEA‐TYPE IBS patients and found that symptoms of some patients improved after treatment . Langlois L reported that anorectal dilatation (acute visceral hypersensitivity model) and SNS on normal SD rats could improve their visceral hypersensitivity induced by anorectal dilatation …”
Section: Introductionmentioning
confidence: 99%
“…9 Langlois L reported that anorectal dilatation (acute visceral hypersensitivity model) and SNS on normal SD rats could improve their visceral hypersensitivity induced by anorectal dilatation. 10 Nerve growth factor (NGF) is one member of the neurotrophic factor family. It is widely distributed in the central nervous system, autonomic nervous system and intestinal nervous system.…”
Section: Introductionmentioning
confidence: 99%